2022
DOI: 10.3390/ijms23137303
|View full text |Cite
|
Sign up to set email alerts
|

Connexin and Pannexin Large-Pore Channels in Microcirculation and Neurovascular Coupling Function

Abstract: Microcirculation homeostasis depends on several channels permeable to ions and/or small molecules that facilitate the regulation of the vasomotor tone, hyperpermeability, the blood–brain barrier, and the neurovascular coupling function. Connexin (Cxs) and Pannexin (Panxs) large-pore channel proteins are implicated in several aspects of vascular physiology. The permeation of ions (i.e., Ca2+) and key metabolites (ATP, prostaglandins, D-serine, etc.) through Cxs (i.e., gap junction channels or hemichannels) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 313 publications
0
5
0
Order By: Relevance
“…ECs are pivotal in maintaining vascular homeostasis through the regulation of permeability and vasoconstriction, both of which are tightly controlled by cytosolic Ca 2+ ([Ca 2+ ] c ) levels. In postcapillary veins, a [Ca 2+ ] c increase is crucial for promoting hyperpermeability [24–27], whereas in arterioles, [Ca 2+ ] c mediates the response to vasoactive agents such as nitric oxide (NO), endothelium hyperpolarizing factor, and endothelin‐1 [5]. Given the importance of Ca 2+ signaling in endothelial function, understanding how different matrix gels may influence Ca 2+ responses to endothelium agonists is of significant interest.…”
Section: Resultsmentioning
confidence: 99%
“…ECs are pivotal in maintaining vascular homeostasis through the regulation of permeability and vasoconstriction, both of which are tightly controlled by cytosolic Ca 2+ ([Ca 2+ ] c ) levels. In postcapillary veins, a [Ca 2+ ] c increase is crucial for promoting hyperpermeability [24–27], whereas in arterioles, [Ca 2+ ] c mediates the response to vasoactive agents such as nitric oxide (NO), endothelium hyperpolarizing factor, and endothelin‐1 [5]. Given the importance of Ca 2+ signaling in endothelial function, understanding how different matrix gels may influence Ca 2+ responses to endothelium agonists is of significant interest.…”
Section: Resultsmentioning
confidence: 99%
“…11,63 As a result, Panx channels are associated with a wide range of cellular physiological and pathophysiological functions. 17,64 Studies demonstrated that Panxs participate in various biological processes, including inflammation, 8,65 ATP signaling, longrange Ca 2+ wave propagation, 66 synaptic plasticity regulation, 67 vascular homeostasis, 68 and neurotoxicity. 7 Additionally, Panxs may contribute to tumor suppression, ischemic cell death, atherosclerosis, apoptosis, 11,69 human immunodeficiency virus (HIV), and epileptic seizures.…”
Section: Panxs Formed Channelsmentioning
confidence: 99%
“…TRPV4-activation induced a strongly ethidium uptake in ECs during the time (Figure 2D). Either inhibition of NO production with 100 µM L-NAME or the blockade of Cx43 hemichannels with 50 µM β-glycyrrhetinic acid (β-GA) or 50 µM Gap19-TAT, a specific Cx43 hemichannel blocker 15,16,24,25 , significantly reduced dye uptake increases. (Figure 2D).…”
Section: Trpv4 Associates Closely With Cx43 and Its Activation Promot...mentioning
confidence: 99%
“…ECs were incubated in MOPS-buffered physiological saline solution (pH 7.4) containing 5 μM ethidium bromide to assess hemichannel activity a well-established method to evaluate connexin hemichannel function 14,16,24,75,76 . The opening of Cx hemichannels was evaluated by tracking the uptake of ethidium over time.…”
Section: Hemichannel Activitymentioning
confidence: 99%